Impact of beam angle choice on pencil beam scanning breath-hold proton therapy for lung lesions. (4th May 2017) - Gorgisyan, Jenny; Perrin, Rosalind; Lomax, Antony J.; Persson, Gitte F.; Josipovic, Mirjana; Engelholm, Svend Aage; Weber, Damien C.; Munck af Rosenschold, Per
Abstract: Introduction: The breath-hold technique inter alia has been suggested to mitigate the detrimental effect of motion on pencil beam scanned (PBS) proton therapy dose distributions. The aim of this study was to evaluate the robustness of incident proton beam angles to day-to-day anatomical variations in breath-hold. Materials and methods: Single field PBS plans at five degrees increments in the transversal plane were made and water-equivalent path lengths (WEPLs) were derived on the planning breath-hold CT (BHCT) for 30 patients diagnosed with locally-advanced non-small cell lung cancer (NSCLC), early stage NSCLC or lung metastasis. Our treatment planning system was subsequently used to recalculate the plans and derive WEPL on a BHCT scan acquired at the end of the treatment. Changes to the V95%, D95 and mean target dose were evaluated. Results: The difference in WEPL as a function of the beam angle was highly patient specific, with a median of 3.3 mm (range: 0.0–41.1 mm). Slightly larger WEPL differences were located around the lateral or lateral anterior/posterior beam angles. Linear models revealed that changes in dose were associated to the changes in WEPL and the tumor baseline shift ( p  < 0.05). Conclusions: WEPL changes and tumor baseline shift can serve as reasonable surrogates for dosimetric uncertainty of the target coverage and are well-suited for routine evaluation of plan robustness. The two lateral beam angles are not recommended to use for PBS proton therapy of lung cancer patients treated in breath-hold, due to the poor robustness for several of the patients evaluated.